Modified aramid fiber, high-strength, high-uniformity and high-water-absorptivity aramid paper as well as preparation method and application of high-strength, high-uniformity and high-water-absorptivity aramid paper

Modifying aramid fibers through bacterial cellulose and foam molding technology solves the problems of hydrophobicity and easy agglomeration on the surface, and high-strength, high uniformity and high water absorption aramid paper is prepared, which broadens its application range.

CN119392532AActive Publication Date: 2025-02-07SOUTH CHINA UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411525605.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The hydrophobicity and prone agglomeration problems of the surface of aramid fibers limit their use in application scenarios where high strength, high hydrophilicity and good liquid absorption capacity are required.

Method used

By combining bacterial cellulose and foam molding technology, bacterial cellulose adheres to the surface of aramid fiber to increase hydrophilic groups, improve dispersion, and use foam molding technology to prepare high-strength, high uniformity and excellent water absorption aramid paper with high strength, high uniformity and excellent water absorption .

Benefits of technology

It significantly improves the strength, uniformity and water absorption of aramid paper, and has good absorption capacity for specific liquids, broadening the application range of aramid fiber and its paper products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392532A_ABST
    Figure CN119392532A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of modification of high-performance fiber materials and preparation of specialty paper, and discloses a modified aramid fiber, high-strength, high-uniformity and high-water-absorption aramid paper and a preparation method and application of the modified aramid fiber and the high-strength, high-uniformity and high-water-absorption aramid paper. The modified aramid fiber comprises bacterial cellulose and aramid fiber in a mass ratio of (0.1-1.5): (2-15). The aramid paper is prepared from the following components in parts by weight: 2 to 16.5 parts of modified aramid fiber, 0.16 to 1.2 parts of hot melting fiber, 0.4 to 2 parts of surfactant and 0.01 to 0.1 part of dispersing agent. Hydrophilic groups on the surfaces of the aramid fibers are effectively increased by utilizing interaction between the bacterial cellulose and the aramid fibers, the prepared aramid paper is high in strength, and compared with aramid paper not modified by the bacterial cellulose, the tensile property is remarkably improved by 244%-1294%, and the tensile strength of the aramid paper is greatly improved. And meanwhile, good uniformity and greatly enhanced water absorption are shown. In addition, the aramid paper has excellent absorption capacity on silica sol, and the application prospect is extremely wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance fiber material modification and special paper preparation, and relates to a modified aramid fiber, a high-strength, high-uniformity, high-water-absorbent aramid paper, and a preparation method and application thereof. Background Art

[0002] As a high-performance synthetic fiber, aramid fiber has excellent high modulus, high strength, and excellent heat resistance and flame retardancy. It has shown wide application potential in many fields such as aerospace, building materials, and sports equipment. Its unique molecular structure and chemical stability make aramid fiber an ideal choice for many high-tech products and industrial applications. However, despite the many advantages of aramid fiber, its surface hydrophobicity and easy agglomeration problems limit its use in certain specific application scenarios to a certain extent. Especially in those occasions where materials are required to have high strength or high hydrophilicity and good liquid absorption capacity, such as biomedical materials, filter media, and aerogel composite materials, the hydrophobicity and easy agglomeration of aramid fibers have become obstacles that cannot be ignored. In order to solve these problems, researchers have tried a variety of methods. Patent CN 113389080 B uses aramid nanofiber dispersion to modify aramid chopped fibers, and constructs a multi-level micro / nano-level rough structure on the surface of aramid fibers to obtain composite fibers coated with aramid nanofibers. This method effectively improves the strength of aramid paper. Unfortunately, however, although this method enhances the strength, the water absorption problem of aramid paper has not been solved. Another patent, CN 114481677B, obtains modified para-aramid crude fiber by polymerization of paraphenylenediamine, terephthaloyl chloride and a fluorescent unit with aggregation-induced emission characteristics, followed by stirring, crushing, washing and drying. Although this method improves the mechanical strength of aramid paper, the problems of uniformity and water absorption have not been properly solved. Therefore, in the process of preparing aramid paper, how to effectively improve the strength, uniformity, water absorption and absorption capacity of aramid paper for specific liquids has become a key technical challenge to broaden the application scope of aramid fibers and their paper products. Summary of the invention

[0003] In view of the problems of aramid fiber surface hydrophobicity, easy agglomeration, and water absorption of aramid paper, the primary purpose of the present invention is to provide a modified aramid fiber.

[0004] Another object of the present invention is to provide an aramid paper with high strength, high uniformity and high water absorption.

[0005] Another object of the present invention is to provide a method for preparing aramid paper with high strength, high uniformity and high water absorption.

[0006] Another object of the present invention is to provide the application of the above-mentioned high-strength, high-uniformity and high-absorbency aramid paper.

[0007] The present invention combines bacterial cellulose and foam molding technology, increases hydrophilic groups by attaching bacterial cellulose to the surface of aramid fibers, improves dispersibility, and uses foam molding technology to prepare aramid paper with high strength, high uniformity and excellent water absorption.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] A modified aramid fiber, comprising bacterial cellulose and aramid fiber, wherein the mass ratio of the bacterial cellulose to the aramid fiber is 0.1-1.5:2-15, more preferably 0.1-0.5:5;

[0010] The hydroxyl groups of the bacterial cellulose are combined with the functional groups on the surface of the aramid fiber by hydrogen bonds.

[0011] The functional groups on the surface of the aramid fiber include but are not limited to phenolic hydroxyl groups and carboxyl groups.

[0012] Preferably, the aramid fiber has a length of 3 to 9 mm and a moisture content of 4 to 5% m / m;

[0013] Preferably, the bacterial cellulose has a diameter of 20 to 150 nm and a length of >20 μm.

[0014] A high-strength, high-uniformity, high-absorbency aramid paper comprises the above-mentioned modified aramid fiber, and the components are as follows in parts by weight:

[0015]

[0016]

[0017] Preferably, the surfactant is at least one of amine gemini quaternary ammonium salt, sodium dodecyl sulfate and dodecyl dimethyl amine oxide.

[0018] Preferably, the dispersant is polyethylene oxide.

[0019] The hot-melt fiber has a melting point of 90 to 110° C., a diameter of 10 to 15 μm, and a length of 3 to 5 mm.

[0020] Preferably, the hot-melt fiber is added in an amount of 8 wt.% of the aramid fiber.

[0021] Preferably, the aramid paper has a basis weight of 278 to 556 g / m 2 .

[0022] Preferably, the tensile stress of the aramid paper is 0.1-3 MPa.

[0023] Preferably, the aramid paper has a uniformity value of 70.0-120.

[0024] A method for preparing high-strength, high-uniformity, and high-absorbency aramid paper is prepared by foam molding technology, comprising the following steps:

[0025] (1) Aramid fiber, hot-melt fiber, and dispersant are added to 1000 parts by weight of water, and after the fiber is dispersed, a bacterial cellulose dispersion is added, the mixture is allowed to stand, and the mixture is dispersed again for a period of time to obtain a mixed solution;

[0026] (2) pouring the mixed liquid into a foaming device, adding a surfactant, stirring and foaming with a stirrer, and pouring it into a molding device after stopping the stirring, vacuum extruding it into wet aramid paper, and drying it to obtain high-strength, high-uniformity, and high-absorbency aramid paper.

[0027] Preferably, the decomposition speed in step (1) is 4000-6000 rpm;

[0028] The fiber deflashing time is 110 to 130 seconds, and the fiber deflashing time is 80 to 100 seconds.

[0029] Preferably, the bacterial cellulose dispersion in step (1) is obtained by treating bacterial cellulose with a 3.5wt.% NaOH solution and then dispersing it at high speed, and the concentration of the bacterial cellulose dispersion is 0.8wt.%.

[0030] Preferably, the stirring speed in step (2) is 1500-2000 rpm, and the foaming time is 5-15 min.

[0031] The application of the above-mentioned high-strength, high-uniformity and high-absorbency aramid paper in aerogel composite materials.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0033] (1) The aramid paper prepared by the present invention has high strength, and its tensile properties are improved by 244% to 1294% compared with the aramid paper not modified by bacterial cellulose, and its uniformity is good, its water absorption is significantly improved, and it has good absorption capacity for silica sol.

[0034] (2) In the present invention, the decomposition and polyethylene oxide can disperse part of the aramid fibers, and the tiny bubbles in the foam molding play a physical barrier role on the aramid fibers. When the aramid fibers are uniformly dispersed in the foam, the foam bubbles can limit the free movement of the fibers and prevent the uniformly dispersed aramid fibers from flocculating and settling again. This physical barrier effect helps the fibers maintain a uniformly dispersed state.

[0035] (3) In the present invention, the stability of the foam needs to be controlled so that it is kept within an appropriate half-life range to achieve the best fiber dispersion effect. The bacterial cellulose adsorbed on the surface of the aramid fiber is attached to the hydrophilic end of the surfactant through the hydroxyl group to form a three-dimensional network structure, which can effectively prevent the rupture and aggregation of bubbles.

[0036] (4) The hydroxyl groups of the bacterial cellulose in the present invention will hydrogen bond with the functional groups (such as phenolic hydroxyl groups, carboxyl groups, etc.) on the surface of the aramid fiber. This hydrogen bonding is a strong intermolecular force that helps the bacterial cellulose to be stably adsorbed on the surface of the aramid fiber.

[0037] (5) During the foam forming process, the present invention controls the foam forming conditions so that the bacterial cellulose can not only effectively stabilize the foam and improve the ability of the foam forming technology to disperse the aramid fiber, but also be evenly and firmly adsorbed on the surface of the aramid fiber to increase the hydrophilic groups on the surface of the aramid fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the half-life diagram of foam slurry (containing aramid fiber);

[0039] Figure 2 It is a direct view of aramid paper (Example 4);

[0040] Figure 3 SEM images of bacterial cellulose (a, b), aramid fiber (c, d), modified aramid fiber (e, f), unmodified aramid paper (g) and modified aramid paper (h);

[0041] Figure 4 Surface images of aramid fibers treated with a dye (the dye can dye bacterial cellulose) (a and b are unmodified aramid fibers, and c and d are modified aramid fibers);

[0042] Figure 5 This is the tensile performance diagram of aramid paper;

[0043] Figure 6 This is the evenness diagram of aramid paper;

[0044] Figure 7 This is a graph showing the water absorption capacity of aramid paper;

[0045] Figure 8 This is a graph showing the ability of aramid paper to absorb silica sol. DETAILED DESCRIPTION

[0046] In order to further understand the present invention, the embodiments of the present invention will be further described in detail below in combination with examples and comparative examples, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques can be referred to.

[0047] Bacterial cellulose was purchased from Guilin Qihong Technology Co., Ltd. The manufacturer treated it with 3.5wt.% NaOH solution and then dispersed it at high speed to obtain a bacterial cellulose dispersion with a dispersion concentration of 0.8wt.%. The diameter of the bacterial cellulose was 20-150nm and the length was >20μm.

[0048] Aramid fiber, length 6mm, moisture content 4.5% m / m, m / m is the mass ratio, that is, 4.5g of aramid fiber is moisture per 100g.

[0049] Hot-melt fiber, melting point is 100°C, diameter is 10-15μm, and length is 4mm.

[0050] Example 1

[0051] (1) In parts by weight, 5 parts of aramid fiber, 0.4 parts of hot-melt fiber, and 0.04 parts of polyethylene oxide were added to 1000 parts of water, and the fibers were deflaked by a deflaker for 120 seconds. After standing for 2 hours, the deflaker was used to deflake the fibers again for 90 seconds at a deflaking speed of 5000 rpm to obtain a mixed solution.

[0052] (2) The mixed solution was poured into a foaming device, and 0.8 parts of dodecyl dimethyl amine oxide was added. The mixture was stirred and foamed at 1800 rpm for 10 minutes. The stirring paddle used for stirring was a three-layer three-blade stirring paddle. After stopping the stirring, the mixture was poured into a molding device, and vacuum extruded into wet aramid paper at 0.1 MPa. The mixture was dried in an oven at 130° C. for 1 hour to obtain aramid paper with a basis weight of 326 g / cm 2 .

[0053] Example 2

[0054] (1) In parts by weight, 5 parts of aramid fiber, 0.4 parts of hot-melt fiber, and 0.04 parts of polyethylene oxide were added to 1000 parts of water, and the fibers were deflaked by a deflaker for 120 seconds, left to stand for 2 hours, and 12.5 parts of bacterial cellulose dispersion (equivalent to 0.1 parts of bacterial cellulose) were added, and the deflaker was used to deflake for another 90 seconds at a deflaking speed of 5000 rpm to obtain a mixed solution including 5.1 parts of modified aramid fiber.

[0055] (2) The mixed solution was poured into a foaming device, and 0.8 parts of dodecyl dimethyl amine oxide was added. The mixture was stirred and foamed at 1800 rpm for 10 minutes. The stirring paddle used for stirring was a three-layer three-blade stirring paddle. After stopping the stirring, the mixture was poured into a molding device, and vacuum extruded into wet aramid paper at 0.1 MPa. The mixture was dried in an oven at 130° C. for 1 hour to obtain aramid paper with a basis weight of 330 g / cm 2 .

[0056] Example 3

[0057] (1) In parts by weight, 5 parts of aramid fiber, 0.4 parts of hot-melt fiber, and 0.04 parts of polyethylene oxide were added to 1000 parts of water, and the fibers were deflaked by a deflaker for 120 seconds, left to stand for 2 hours, and 37.5 parts of bacterial cellulose dispersion (equivalent to 0.3 parts of bacterial cellulose) were added, and the deflaker was used to deflake again for 90 seconds at a deflaking speed of 5000 rpm to obtain a mixed solution including 5.3 parts of modified aramid fiber.

[0058] (2) The mixed solution was poured into a foaming device, and 0.8 parts of dodecyl dimethyl amine oxide was added. The mixture was stirred and foamed at 1800 rpm for 10 minutes. The stirring paddle used for stirring was a three-layer three-blade stirring paddle. After stopping the stirring, the mixture was poured into a molding device, and vacuum extruded into wet aramid paper at 0.1 MPa. The mixture was dried in an oven at 130° C. for 1 hour to obtain aramid paper with a basis weight of 333 g / cm 2 .

[0059] Example 4

[0060] (1) In parts by weight, 5 parts of aramid fiber, 0.4 parts of hot-melt fiber, and 0.04 parts of polyethylene oxide were added to 1000 parts of water, and the fibers were deflaked by a deflaker for 120 seconds, left to stand for 2 hours, and 62.5 parts of bacterial cellulose dispersion (equivalent to 0.5 parts of bacterial cellulose) were added, and the deflaker was used to deflake again for 90 seconds at a deflaking speed of 5000 rpm to obtain a mixed solution including 5.5 parts of modified aramid fiber.

[0061] (2) The mixed solution was poured into a foaming device, and 0.8 parts of dodecyl dimethyl amine oxide was added. The mixture was stirred and foamed at 1800 rpm for 10 minutes. The stirring paddle used for stirring was a three-layer three-blade stirring paddle. After stopping the stirring, the mixture was poured into a molding device, and vacuum extruded into wet aramid paper at 0.1 MPa. The mixture was dried in an oven at 130° C. for 1 hour to obtain aramid paper with a basis weight of 340 g / cm 2 .

[0062] Comparative Example 1

[0063] (1) In parts by weight, 5 parts of aramid fiber, 0.4 parts of hot-melt fiber, and 0.04 parts of polyethylene oxide were added to 1000 parts of water, and the fibers were deflaked by a deflaker for 120 seconds, left to stand for 2 hours, and 62.5 parts of bacterial cellulose dispersion (equivalent to 0.5 parts of bacterial cellulose) were added, and the deflaker was used to deflake again for 90 seconds at a deflaking speed of 5000 rpm to obtain a mixed solution including 5.5 parts of modified aramid fiber.

[0064] (2) Aramid paper was prepared by a wet forming method. First, the water level in the sheet making machine reached a preset height, and then the mixed liquid was slowly injected. When the water level approached the maximum capacity, the water addition was stopped and the drainage procedure was started. Then, the drainage and forming operations were performed. Finally, the aramid paper was dried at 130°C for 1 hour to obtain a 340 g / cm3 aramid paper.2 .

[0065] Test Example 1

[0066] The mixed solution of Examples 1 to 5 was stirred at 1800 rpm for 10 min to obtain a foam slurry containing aramid fibers. The foam stability was tested using the Waring-Blender method, and the results are as follows:

[0067] Figure 1 This is a half-life diagram of foam slurry (containing aramid fiber). As can be seen from the figure, in Example 1, the half-life of the foam slurry is 380s; in Example 2, the half-life of the foam slurry is 420s; in Example 3, the half-life of the foam slurry is 448s; in Example 4, the half-life of the foam slurry is 467s. The results show that the addition of bacterial cellulose can improve the stability of the foam and prevent the foam from breaking and agglomerating in a short period of time. Bacterial cellulose has a unique three-dimensional network structure, which can prevent the loss of liquid on the bubble surface and the merging of bubbles, and increase the bubble stability time.

[0068] Test Example 2

[0069] The aramid papers prepared in Examples 1 to 5 were observed visually and by SEM, and the test results are as follows:

[0070] Figure 2 This is a direct view of aramid paper (Example 4). The surface of the aramid paper is uniform and smooth, with almost no roughness. This surface improves the aesthetics of the aramid paper. Figure 3 (a) and Figure 3 (b) is the SEM image of bacterial cellulose. The fibers in bacterial cellulose are densely intertwined to form a complex three-dimensional network structure with tiny gaps distributed between the networks. Figure 3 (c) and Figure 3 (d) is the SEM image of aramid fiber. The surface of aramid fiber is smooth without obvious texture or uneven areas. Figure 3 (e) and Figure 3 (f) is the SEM image of the modified aramid fiber. It can be seen from the figure that the bacterial cellulose wraps the surface of the aramid fiber through hydrogen bonds to form a dense fiber membrane, indicating that the bacterial cellulose has successfully modified the surface of the aramid fiber and increased the hydrophilic groups on the surface of the aramid fiber. Figure 3 (g) is the SEM image of unmodified aramid paper (without bacterial cellulose), in which the aramid fibers are intertwined and stacked layer by layer to form a large number of gaps. Figure 3(h) is the SEM image of the modified aramid paper, in which it can be clearly observed that the bacterial cellulose is tightly attached to the surface of the aramid fiber, forming a strong bond. More importantly, the presence of bacterial cellulose not only effectively fills the tiny gaps in the internal structure of the aramid paper and improves the internal structure of the material, but also significantly enhances the connectivity between the aramid fibers through its excellent bonding ability.

[0071] Test Example 3

[0072] A single fiber was taken out from the aramid paper prepared in Examples 1 to 5 and dyed with Graff dye (the dye can dye bacterial cellulose). Its appearance was observed using a polarizing microscope. The test results are as follows:

[0073] Figure 4 (a) and Figure 4 (b) is unmodified aramid fiber (does not contain bacterial cellulose). The results show that the surface of aramid fiber cannot be dyed by dyes, and it appears uneven with alternating light and dark colors. Figure 4 (c) and Figure 4 (d) is modified aramid fiber (containing bacterial cellulose). The fiber surface is dark yellow. The uniform distribution of dark yellow also suggests that the coverage of bacterial cellulose on the surface of aramid fiber is comprehensive and uniform. As an intuitive visual sign, it strongly proves that bacterial cellulose has been successfully adsorbed and attached to the surface of aramid fiber.

[0074] Test Example 4

[0075] The tensile properties of the aramid papers prepared in Examples 1 to 5 and Comparative Example 1 were tested, and the test results are as follows:

[0076] Figure 5The tensile performance test results of aramid paper are shown. The results show that the tensile stress of the unmodified aramid paper (Example 1) is 0.18MPa, and the maximum force it can withstand is 6.4N. In contrast, the modified aramid paper has significant improvements in tensile stress and maximum force during breaking: the tensile stress of Example 2 increases to 0.62MPa, and the maximum force it can withstand reaches 22.27N, and the tensile stress strength increases by 244%; the tensile stress of Example 3 is 1.73MPa, and the maximum force it can withstand is 62.17N, and the tensile stress strength increases by 861%; the tensile stress of Example 4 is as high as 2.51MPa, and the maximum force it can withstand is 90.39N, and the tensile stress strength increases by 1294%; the tensile stress of Comparative Example 1 reaches 1.89MPa, and the maximum force it can withstand is 78.6N, and the tensile stress strength increases by 950%. The strength of aramid paper obtained by another authorized patent (patent number CN112663382A) does not exceed 20 N. The aramid paper strength enhancement method adopted by the present invention, wherein the effects in Examples 2 to 4 are better than those in the above patent.

[0077] Test Example 5

[0078] The aramid papers prepared in Examples 1 to 5 and Comparative Example 1 were tested for uniformity. The smaller the uniformity value, the better the uniformity of the aramid paper. The test results are as follows:

[0079] Figure 6 The test results of the uniformity of aramid paper are shown. The uniformity value of Example 1 is 116.2; the uniformity value of Example 2 is 112.6; the uniformity value of Example 3 is 97.9; the uniformity value of Example 4 is 79.0; and the uniformity value of Comparative Example 1 is 244.2. The test results show that the surface modification of aramid fiber helps its dispersion, and the aramid paper prepared by foam molding has good uniformity. This treatment method solves the problem of easy agglomeration of aramid fibers.

[0080] Test Example 6

[0081] The aramid papers prepared in Examples 1 to 5 and Comparative Example 1 were tested for their water absorption and silica sol absorption capabilities. The test results are as follows:

[0082] Figure 7The test results of the water absorption capacity of aramid paper are shown. The aramid paper is precisely cut and samples weighing between 1 and 1.1 g are carefully selected. Subsequently, it is placed in a container filled with 50 ml of water and waited for 60 seconds to ensure that the sample is fully soaked. After that, the sample is carefully taken out and the excess water on its surface is gently removed with filter paper, followed by accurate measurement and recording of the weight increase after absorbing water. Example 1 absorbs 12.5 g of water; Example 2 absorbs 14 g of water; Example 3 absorbs 14.8 g of water; Example 4 absorbs 14.9 g of water; and Comparative Example 1 absorbs 14 g of water. This series of test results strongly proves that the surface modification of aramid fiber has significantly improved the water absorption performance of aramid paper and improved the hydrophobicity of aramid fiber.

[0083] Figure 8 The test results of the silica sol absorption capacity of aramid paper are shown. The aramid paper is precisely cut, and a aramid paper sample with a length of 13 cm and a width of 1.5 cm is selected. The top of the sample is fixed with a clamp, and the bottom is below the bottom. The timing starts when the bottom contacts the liquid, and the silica sol liquid is removed after 180 seconds, and the absorption height is measured and recorded. The results show that the height of the silica sol liquid absorbed by Example 1 reaches 2.9 cm; the height of the silica sol liquid absorbed by Example 2 is 5 cm; the height of the silica sol liquid absorbed by Example 3 is 5.5 cm; the height of the silica sol liquid absorbed by Example 4 is 6.8 cm; the height of the silica sol liquid absorbed by Comparative Example 1 is 5.8 cm. This series of test data not only fully verifies that aramid paper has a good absorption capacity for silica sol, but also further proves that the surface treatment technology of this patent can significantly improve the absorption performance of aramid paper for silica sol liquid, providing a strong scientific basis for the application in related fields such as aerogel composite materials.

[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A modified aramid fiber, characterized in that: It comprises bacterial cellulose and aramid fiber, wherein the mass ratio of the bacterial cellulose to the aramid fiber is 0.1-1.5:2-15; The hydroxyl groups of the bacterial cellulose are combined with the functional groups on the surface of the aramid fiber by hydrogen bonds.

2. The modified aramid fiber according to claim 1, characterized in that The bacterial cellulose has a diameter of 20 to 150 nm and a length of >20 μm; The aramid fiber has a length of 3 to 9 mm and a moisture content of 4 to 5% m / m.

3. A high-strength, high-uniformity, high-absorbency aramid paper, characterized in that: The modified aramid fiber according to claim 1 or 2 comprises the following components in parts by weight:

4. The high-strength, high-uniformity, high-absorbency aramid paper according to claim 3, characterized in that: In parts by weight, the components are as follows:

5. The high-strength, high-uniformity, high-absorbency aramid paper according to claim 3 or 4, characterized in that: The surfactant is at least one of amine gemini quaternary ammonium salt, sodium dodecyl sulfate and dodecyl dimethyl amine oxide.

6. The high-strength, high-uniformity, high-absorbency aramid paper according to claim 3 or 4, characterized in that: The hot-melt fiber has a melting point of 90 to 110° C., a diameter of 10 to 15 μm, and a length of 3 to 5 mm.

7. The method for preparing the high-strength, high-uniformity, high-absorbency aramid paper according to any one of claims 3 to 6, characterized in that: The foam molding technology is used to prepare the product, which includes the following steps: (1) Aramid fiber, hot-melt fiber, and dispersant are added to 1000 parts by weight of water, and after the fiber is dispersed, a bacterial cellulose dispersion is added, the mixture is allowed to stand, and the mixture is dispersed again for a period of time to obtain a mixed solution; (2) pouring the mixed liquid into a foaming device, adding a surfactant, stirring and foaming with a stirrer, and pouring it into a molding device after stopping the stirring, vacuum extruding it into wet aramid paper, and drying it to obtain high-strength, high-uniformity, and high-absorbency aramid paper.

8. The method for preparing high-strength, high-uniformity, and high-absorbency aramid paper according to claim 7, characterized in that: The decomposition speed in step (1) is 4000-6000 rpm; The fiber deflashing time is 110 to 130 seconds, and the fiber deflashing time is 80 to 100 seconds.

9. The method for preparing high-strength, high-uniformity, and high-absorbency aramid paper according to claim 7, characterized in that: The stirring speed in step (2) is 1500-2000 rpm, and the foaming time is 5-15 min.

10. Use of the high-strength, high-uniformity, high-absorbency aramid paper according to any one of claims 3 to 6 in aerogel composite materials.

Citation Information

Patent Citations

  • High-mechanical-strength aramid insulating paper as well as preparation method and application thereof

    CN112663382A

  • A method for modifying aramid fibers

    CN113389080B

  • Preparation method and application of bacterial cellulose / aramid nano fiber composite aerogel

    CN108727639A

  • Foam stabilizer as well as preparation method and application thereof

    CN117401929A

  • Absorbent paper and its production

    JP1996232189A